The oral histone deacetylase inhibitor LBH589 is a potential and promising therapeutic agent in multiple myeloma after at least two lines of chemotherapy including bortezomib or lenalidomide - Schmitt, Stefan; Ho, Anthony Dick; Goldschmidt, Hartmut (Onkologie, 2010)
Multiple myeloma as the second most common hematological malignancy is characterized by proliferation of monoclonal plasma cells. This entity still remains a non-curable disorder leading, amongst others, to complications as myeloma bone disease, bleeding events, kidney failure and neurological impairment. LBH589 is a histone deacetylase inhibitor with an epigenetic mechanism of action and the potential for treatment in myeloma. We report here about the successful treatment of a 44-year-old woman suffering from progressive myeloma with LBH589 after five different chemotherapies. During the 9 years after first diagnosis of myeloma in April 2000, our patient twice underwent an autologous stem cell transplantation and was also treated with the new substances bortezomib, thalidomide and lenalidomide.